Heidegger’s question of being and question on the art - Radovanović, Saša Ž (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2015)
This paper investigates the problem of relation between the question of Being and the question of art in the thought of Martin Heidegger. His thought trajectory comprises two different forms of question considering Being. He calls the first one the main question. This form he considers to be metaphysical since it can be traced in traditional philosophical thought back to Plato and Nietzsche, or the thought of the first beginning. The second form is the fundamental question about Being which leads to overcoming of metaphysical understanding of Being and belongs to the thought of the second beginning. This second form, according to his words at the seminar at Le Thor appears in three forms along his thought trajectory; firstly, as a fundamental ontological question of the meaning of Being, then, as significant historical question concerning the truth of Being, and finally, as a topological question concerning the space and spatiality of Being. His position concerning art needs to be considered in the light of fundamental issue of Being in his thought.